(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Performance of overall finance of business can be measured by using the historical data related to finance and the future soundness and health of the company. Finance is important aspect of business need to check in determining that a company and organization is how much capable, stable, liquid and solvent. For the purpose of checking company specific performance a researcher, study its financial statement and income statement. On the other hand researcher may check or compare the past performance and trend of the company to get the reliable results of the analysis. Trade creditors, suppliers, investors, management and government is interested to know the financial performance of the company. Analysis of finance supports government organizations to stable the taxation system and any the company can check its own level of performance by using the analysis of financial statements time to time. Further the investors of companies can also draw an idea and make up mind to invest their funds in any specified company as their funds produce a worth.